The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11912-008-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells in solid cancer: Tumor marker of clinical relevance?

Abstract: Circulating tumor cells (CTC) can be detected in the peripheral blood of patients with a variety of solid cancers. Because of their very low frequency, these tumor cells are not easily detected using conventional cytology methods. In the past decade, numerous groups have attempted to detect CTC of solid malignancies using the highly sensitive reverse transcriptase polymerase chain reaction, which has been shown to be superior to conventional techniques. However, the biological significance of CTC and the thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…A large body of clinical studies has indicated that circulating tumor cells (CTC) in peripheral blood are an important prognostic marker for cancers (1)(2)(3)(4)(5). The presence of CTC in the peripheral blood of patients has been implicated in tumor progression and metastasis development.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of clinical studies has indicated that circulating tumor cells (CTC) in peripheral blood are an important prognostic marker for cancers (1)(2)(3)(4)(5). The presence of CTC in the peripheral blood of patients has been implicated in tumor progression and metastasis development.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who undergo potentially curative surgeries retain the risk of recurrence that originates from microscopic tumor residues known as minimal residual disease (MRD). MRD can affect different body compartments, including bone marrow, lymph nodes, and peripheral blood 7. Quantitative real‐time polymerase chain reaction (qrt‐PCR) is considered to be the most sensitive method for evaluating gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…These conflicting data might depend on the fact that CK19 and CEA are markers of CTC presence but not necessarily of CTC ability to metastasize: in fact, it is well accepted that only a subset of CTC has the biological potential of giving rise to metastatic deposits, while most CTC ultimately die without being harmful for the host [7]. Accordingly, markers of CTC "aggressiveness" such as Survivin might reveal to be more informative in terms of correlation with patients' prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who had undergone potentially curative surgeries retain the risk of recurrence that originates from microscopic tumor residues known as minimal residual disease (MRD). MRD can affect different body compartments, including the bone marrow, lymph nodes and peripheral blood [7]. In recent years, several studies have focused on the detection of circulating tumor cells (CTC) with respect to their clinical implications for patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%